Surgical treatment of pterygium using a high-frequency electric welding of biological tissue fixation limbal — conjunctival autograft (Ukrainian Journal of Ophthalmology, 2026)
Importanceof work is determined by an increase in the efficiency of surgical treatment of pterygium by reducing postoperative complications. Purpose. To study the effect of surgical treatment pterygium using techniques of high-frequency electric welding for intraoperative connecting limbal conjunctival autograft. Methods. Surgical treatment of 105 patients (105 eyes) with pterygium varying degrees. 73 patients (73 eyes) — a group of studies that were conducted surgical treatment of pterygium using free limbal conjunctival autograft, (patent of Ukraine № u 201406922). 32 patients (32 eyes) were the comparison group and were operated by other methods (Mc Reynolds, Arlt et al.) The research group was divided into study and control groups. Patients in the control group — 39 patients (39 eyes) wiht suture fixation of free limbal conjunctival autograft,. 34 patients (34 eyes) study group received surgery with the use of high-frequency electric welding fixing the free limbal conjunctival autograft-modified machine EK-300M1 with bipolar forceps original design. Efficacy was assessed by the incidence of postoperative inflammatory reaction — corneal syndrome, epithelialization of the cornea and of relapse. Results: In the study group (34 patients), which used high-frequency electric welding fabrics for fixing the free limbal conjunctival autograft-early postoperative subjective symptoms associated with an inflammatory response (corneal syndrome), there were 9 eyes (26.5 %) in 9 patients. On day 5, complete epithelialization of the cornea was observed on 30 eyes (88.2 %) of 30 patients. In the control group (39 patients), which used the free suture fixation-conjunctival limbal autograft in 33 eyes of 33 patients (84.6 %) was characterized by severe postoperative corneal syndrome during the first 2–3 days. Complete epithelialization of postoperative corneal erosion was observed on day 5 of 20 eyes (51.3 %) in 20 patients. After 6 months in the study group 73 patients (73 eyes) on the background of the proposed therapy revealed a recurrence of pterygium 6 eyes (8.2 %) in 6 patients in the comparison group, 32 patients (32 eyes) of pterygium recurrence in 9 patients met at 9 eyes (28.1 %), 19.9 % more than in the study group.. Conclusions. The use of free limbal conjunctival autograft-surgical treatment of pterygium allows significantly reduce the risk of recurrence of the disease was 3.4 times (95 % CI 1,1 ? 10,4) compared with other techniques. The use of high-frequency electric welding fabrics for fixing the free limbal conjunctival autograft, can reduce the frequency of clinical manifestations of corneal syndrome on 58,1 % (p
Keywords: pterygium; joints; electric welding; autograft